Study of the Cost Effectiveness of Therapy in Hypertention Patients in Hospital - Yuswantina, Richa; Dyahariesti, Niken; Ambarwati, Diastri Dwi (Universitas Islam Lamongan, 2023)
Hypertension is where the blood pressure is > 140 mmHg and > 90 mmHg. Combination therapy is needed if a single antihypertensive has not been able to control the desired blood pressure target while the cost of treatment is increasing from time to time. The purpose of this study was to determine the cost-effective combination therapy for antihypertensive drugs in hypertensive patients in an inpatient setting. This study is a descriptive study with a pharmacoeconomic analysis approach using the Cost Effectiveness Analysis (CEA) method which was carried out retrospectively. Data were collected using the Total Sampling technique with 93 patients which were then analyzed to determine the cost-effective therapy based on ACER and ICER. The results showed that hypertension was mostly experienced by patients aged 50-60 years, male sex was more than female. HT stage 2 is often experienced by patients. Type II DM is the most common comorbidity. The lowest ACER value is Rp. 65.195.77. The lowest ICER value is Rp. 7.047.2551 when compared with standard therapy, namely CCB + ACEI. The combinations used in the inpatient unit include two combinations of 42 patients (45.16%) three combinations of 37 patients (39.78%), four combinations 6 (6.45%) five combinations of 8 patients (8.6%). The lowest average direct medical cost is the combination of ACEI antihypertensive + Diuretic + -Blocker Rp. 2.765.262. The cost effective therapy based on ACER and ICER values is a combination of Diuretics + CCB + ACEI + Blockers with an ACER value of Rp. 65,195.77 and also dominant.